Seismic isolation of buildings with sliding concave foundation (SCF). - Hamidi, M. (Earthquake engineering & structural dynamics.)
In this paper, a new base isolation system, namely the sliding concave foundation (SCF), is introduced and the behaviour of the buildings using such a system is theoretically investigated. A building supported on the new system behaves like a compound pendulum during seismic excitation. The pendulum behaviour accompanied by the large radius of foundation curvature shifts the fundamental period of the system to a high value (e.g. more than 8 sec), in frequency range where none of the previously recorded earthquakes had considerable energy. This results in a large decrease in the structural responses. Since small friction forces are essential on the contact surfaces, PTFE sheets can be used as sliding surfaces. Although the pure frictional sliding systems have the same efficiency as the SCF, in reducing the responses of the superstructure, the main advantage of the new system is a significant decrease in sliding displacement. The performance of the SCF subjected to a number of harmonic and non harmonic base excitations is studied and its ability to reduce the structural responses is examined. Some numerical examples are solved for a single degree of freedom (SDOF) structure and the responses are compared with the responses of the same SDOF structure on a fixed base or a pure frictional sliding support system. The comparisons confirm the effectiveness of the new system.